Using Motivational Interviewing to reduce threats in conversations about environmental behavior - Klonek, Florian E.; Güntner, Amelie V.; Lehmann-Willenbrock, Nale; Kauffeld, Simone (Frontiers in Psychology, 2015)
Human behavior contributes to a waste of environmental resources and our society is looking for ways to reduce this problem. However, humans may perceive feedback about their environmental behavior as threatening. According to self-determination theory (SDT), threats decrease intrinsic motivation for behavior change. According to self-affirmation theory (SAT), threats can harm individuals’ self-integrity. Therefore, individuals should show self-defensive biases, e.g., in terms of presenting counter-arguments when presented with environmental behavior change. The current study examines how change recipients respond to threats from change agents in interactions about environmental behavior change. Moreover, we investigate how Motivational Interviewing (MI)—an intervention aimed at increasing intrinsic motivation—can reduce threats at both the social and cognitive level. We videotaped 68 dyadic interactions with change agents who either did or did not use MI (control group). We coded agents verbal threats and recipients’ verbal expressions of motivation. Recipients also rated agents’ level of confrontation and empathy (i.e., cognitive reactions). As hypothesized, threats were significantly lower when change agents used MI. Perceived confrontations converged with observable social behavior of change agents in both groups. Moreover, behavioral threats showed a negative association with change recipients’ expressed motivation (i.e., reasons to change). Contrary to our expectations, we found no relation between change agents’ verbal threats and change recipients’ verbally expressed self-defenses (i.e., sustain talk). Our results imply that MI reduces the adverse impact of threats in conversations about environmental behavior change on both the social and cognitive level. We discuss theoretical implications of our study in the context of SAT and SDT and suggest practical implications for environmental change agents in organizations.